Usages culturels de la foret au Sud-Cameroun: rudiments d'ecologie sociale et materiau pour la gestion du pluralisme - Oyono, P.R. (2002)
Based on social ecology, anthropological and policy research conducted on social dimension of natural resources management in Cameroon, this contribution liberates a given number of findings: 1. local communities in Cameroon have both an horizontal (practical) and a vertical (metaphysical) perception of the forest; 2. in the course of the time, they have been manipulating forest resources for cultural uses at the two levels. In that sense, cultural manipulation of forest resources is showing beneath popular narration, withcraft, toponymy and ritual orders. These cultural construction need to be carefully and meaningfully, captured and chanelled in the implementation of Programs and policy design. Because local systems are resilient and can not be emarginated successfully in the issue of forest management, the author calls for a cultural adjustment.